TCRzetadim lymphocytes define populations of circulating effector cells that migrate to inflamed tissues. - Zhang, Z; Gorman, C; Vermi, A; Monaco, C; Foey, A; Owen, S; Amjadi, P; Vallance, A; McClinton, C; Marelli-Berg, F; Isomäki, P; Russell, A; et al. (2007)
The T-cell receptor zeta (TCRzeta) chain is a master sensor and regulator of lymphocyte responses. Loss of TCRzeta expression has been documented in infectious, inflammatory, and malignant diseases, suggesting that it may serve to limit T-cell reactivity and effector responses at sites of tissue damage. These observations prompted us to explore the relationship between TCRzeta expression and effector function in T cells. We report here that TCRzeta(dim) lymphocytes are enriched for antigen-experienced cells refractory to TCR-induced proliferation. Compared to their TCRzeta(bright) counterparts, TCRzeta(dim) cells share characteristics of differentiated effector T cells but use accessory pathways for transducing signals for inflammatory cytokine gene expression and cell contact-dependent pathways to activate monocytes. TCRzeta(dim) T cells accumulate in inflamed tissues in vivo and have intrinsic migratory activity in vitro. Whilst blocking leukocyte trafficking with anti-TNF therapy in vivo is associated with the accumulation of TCRzeta(dim) T cells in peripheral blood, this T-cell subset retains the capacity to migrate in vitro. Taken together, the functional properties of TCRzeta(dim) T cells make them promising cellular targets for the treatment of chronic inflammatory disease.